Investigation of traumatic orthopedic injuries in rugby players of Maranhão. - Rodrigues, Kilza Conceição; Silva, Camila Garcia; Silva, Fabiano Fernandes da; Mangueira, Nilton Maciel; Souza, Renato Aparecido de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Rugby is a sport that is growing in popularity worldwide. However, there are still a limited number of investigations on trauma-orthopedic injuries related to this sportive practice. Objective: To investigate traumatic orthopedic injuries in rugby players of Associação Maranhense de Rugby (AMARU) occurred in the first half of 2013. Method: 22 players were interviewed using a semi-structured questionnaire with 11 questions that addressed, among other issues, the ones related to the type and body region of injury, as well as the demographic of players. The design research meets the characteristics of a cross-sectional study of a descriptive nature. Results: Approximately 50% of rugby players of AMARU reported some trauma-orthopedic. These injuries are primarily associated with the training situation, especially the tackle. Injuries around the shoulder, knee and ankle are the most common. Muscle injury type distention was reported in 50% of players. Finally, in the opinion of the players, the condition of the pitch is the main extrinsic factor that causes injury. Conclusion: Information about trauma and orthopedic injuries of amateur athletes and encourage preventive and training measures for increasing the popularity of this sport grow in our country. From the findings of this study, AMARU can better guide their actions for favoring rugby practice in the state of Maranhão mainly from the perspective of health promotion and social inclusion.